Experimental studies on the effectiveness and robustness of a pounding tuned mass damper for vibration suppression of a submerged cylindrical pipe. Issue 12 (11th May 2017) - Jiang, Jinwei; Zhang, Peng; Patil, Devendra; Li, Hong‐nan; Song, Gangbing
Summary: Pounding tuned mass damper (PTMD) is a novel type of passive damper. The PTMD utilizes collisions or impacts of a tuned mass with viscoelastic materials to efficiently dissipate the vibration energy of primary structures. The previous studies have verified its effective damping performance on a full‐scale subsea jumper and other structures in air. This paper presents the first‐ever experimental verification of a submerged PTMD system for vibration control of pipelike structures underwater. To facilitate the experimental studies, a vertical vibration system consisting of 4 springs and a cylindrical steel pipe was designed and set up in a water tank. Furthermore, a numerical method considering the effect of the added mass is described to estimate the natural frequencies of a submerged cylindrical pipe. Therefore, experimental results demonstrate that the PTMD system is effective and efficient to suppress the forced vibrations of the submerged cylindrical pipe at the tuned frequency and is also robust over a range of detuning frequencies.